2009
DOI: 10.1111/j.1538-7836.2008.03206.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin inhibits tissue factor expression in monocytes

Abstract: Summary. Objectives: Platelets from healthy subjects are inhibited by insulin but type 2 diabetes mellitus (T2DM) platelets have become insulin-resistant, which might explain their hyperactivity. In the present study we investigated whether monocytes are responsive to insulin. Methods and results: LPSinduced tissue factor (TF) upregulation was measured in human monocytes and monocytic THP-1 cells in a factor Xa generation assay.) induced a dose-dependent inhibition in both cell types and in monocytes 100 nmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 34 publications
2
33
0
2
Order By: Relevance
“…A previous study showed that LPS-induced immune response leads to a decrease of intracellular cAMP (55). Another study showed that LPS activates G i , thereby inhibiting AC and formation of cAMP (56). Stimulation with cAMP not only increases Na + transport within 5 min, but also promotes Na,K-ATPase recruitment to the plasma membrane (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that LPS-induced immune response leads to a decrease of intracellular cAMP (55). Another study showed that LPS activates G i , thereby inhibiting AC and formation of cAMP (56). Stimulation with cAMP not only increases Na + transport within 5 min, but also promotes Na,K-ATPase recruitment to the plasma membrane (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy individuals, insulin interferes with the suppression of cAMP and accumulation of this inhibitor attenuates platelet functions and monocyte responses. 9,10 The insulin resistance observed in type 2 diabetes rescues the fall in cAMP, which promotes aggregation, secretion and procoagulant activity in platelets and tissue factor synthesis and interleukin-1β secretion in monocytes. Insulin also inhibits splicing of tissue factor pre-mRNA in platelets adhering to prothrombotic proteins and the loss of insulin responsiveness in type 2 diabetes might well contribute to the thrombogenicity of the platelet plug that forms upon plaque rupture.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that AhR induces signaling pathways that entail ERK, PKA, MMP9 and cAMP, cGMP and Ca 2+ [22]. It has also been shown that AhR is more sensitive to the cAMP signaling pathway [22,23], and that cAMP induces nuclear translocation of the AhR [24]. Thus it appears that the two signaling pathways for regulation of ENaC, cAMP, and cGMP are compartmentalized.…”
Section: Discussionmentioning
confidence: 97%
“…Extracellular signals also interact with GPCR to activate guanylyl cyclases (GC) and increase intracellular cGMP levels. Studies have shown that AhR induces signaling pathways that entail ERK, PKA, MMP9 and cAMP, cGMP and Ca 2+ [22]. It has also been shown that AhR is more sensitive to the cAMP signaling pathway [22,23], and that cAMP induces nuclear translocation of the AhR [24].…”
Section: Discussionmentioning
confidence: 99%